Composite lymphoma with coexistence of diffuse large B-cell lymphoma and anaplastic large cell lymphoma: Diagnostic pitfalls - Meyyappa Devan Rajagopal; Rakhee Kar; Debdatta Basu; Sunu Lazar Cyriac (Wolters Kluwer Medknow Publications, 2017)
Composite lymphoma is a rare tumor composed of two or more distinct lymphomas in the same topographic site or tissue. Several combinations of B-cell non-Hodgkin lymphoma (NHL), T-cell NHL, and Hodgkin lymphoma can occur with different prognoses and treatments. The coexistence of a B-cell NHL and a T-cell NHL is unusual. The exact etiology of composite lymphoma is unknown; however, few mechanisms have been proposed to explain its pathogenesis. The chemotherapeutic protocols are heterogeneous but are essentially targeted against the high-grade component. Most of the cases show worse outcome with a median survival of 12 months. In this article, we report a case of composite lymphoma which was initially diagnosed as diffuse large B-cell lymphoma, and the presence of CD3-positive atypical cells in the bone marrow urged us to re-evaluate the lymph node biopsy following which a focus of Alk-1-positive anaplastic large cell lymphoma was identified.